Risk factors for preterm births in São Luís, Maranhão, Brazil - Vânia Maria de Farias Aragão; Antônio Augusto Moura da Silva; Lívia Farias de Aragão; Marco Antônio Barbieri; Heloísa Bettiol; Liberata Campos Coimbra; Valdinar Sousa Ribeiro
Preterm birth continues to be one of the main causes of neonatal morbidity and mortality. The objective of the present study was to identify risk factors for preterm birth in São Luís, Maranhão, Brazil. The sample consisted of hospital births at 10 public and private hospitals from March 1, 1997 to February 28, 1998. A total of 2,443 live births were randomly selected, excluding multiple deliveries and stillbirths. Preterm birth rate in São Luís was 12.7%. Risk factors for preterm delivery were maternal age below 18 years, family income equal to or less than one minimum wage/ month, primiparity, vaginal delivery at a public hospital, single mothers (or living without a partner), and absence of prenatal care. The following factors remained associated with preterm birth after multivariate analysis to control for confounding: maternal age below 18 years (OR = 1.9), primiparity (OR = 1.5), and failure to appear for scheduled prenatal care visits (OR = 1.5).